Suppression of DMBA-induced carcinogenesis of breast cancer in post initition stage by ethanolic extract of Gynura procumbens (Lour), Merr leaves - Edy Meiyanto; Sri Tasminatun; Sri Susilowati; Retno Murwanti; Sugiyanto . (Indonesian Journal of Pharmacy, 2007)
Gynura procumbens (Lour) Merr., has been shown to suppress lung cancer development in mice and breast cancer development in rat when the extract was given at initiation stage. The aim of this research is to examine the potential of ethanolic extract of G. procumbens to suppress DMBAinduced breast cancer development at early development (post initiation I) and late development (post initiation II). Sprague Dawley Rats were used in this research and were grouped as indicated treatment. Ethanolic extract of G. procumbens was administered into 2 levels of doses, namely 250, 750 mg/kgBW. Tumor development was examined by palpation every week and terminated at week 16th after the end of DMBA treatment. The result showed that extract treatment at the dose of 250, and 750 mg/kgBW at the post initiation I could not reduce tumor incidence but suppressed of tumor multiplicity. However, the treatment at the post initiation II, the extract could not reduce neither incidence nor multiplicity. In conclusion, ethanolic extract of G. procumbens performs potential effect to suppress breast cancer development at the dose of 250 mg/kgBW when administered at the early stage of carcinogenesis.Key words : Carcinogenesis inhibition, G. procumbens, breast cancer, post initiation